Efficacy Respiratory Physiotherapy On Allergic Bronchopulmonary Aspergillosis. A Case Report - Zacarías Sánchez Milá; Jorge Velázquez Saornil; Angélica Campón Chekroun; Elena Sánchez Jiménez; Sonia Gómez Sánchez; Ana Martín Jiménez (International Journal of Physiotherapy, 2022)
Background: Allergic bronchopulmonary aspergillosis (ABPA) is a disease characterized by reversible airway obstruction. The clinical symptomatology involves recurrent episodes predominantly in subjects with asthma, those with cystic fibrosis, and subjects with bronchiectasis. Methods: A respiratory physiotherapy treatment plan of home training with The Acapella DH® provides the oscillatory positive expiratory pressure (OPEP) and POWERbreathe Plus® for two weeks, five days a week, twice a day (10 minutes in the morning and another 10 minutes in the afternoon) and to analyze the effectiveness of respiratory therapy using spirometry, as a treatment for a clinical case suffering from allergic bronchopulmonary aspergillosis, bronchial asthma, and bronchiectasis. Results: The first spirometric assessment carried out on week zero revealed that after the home treatment plan in week one and week two assessments, a significant increase in all spirometric lung function values was assessed with % change, such as Vital Capacity (VC), resulting in week 1 (0.80%) week 2 (1.09%), Tidal Volume (VT) resulting in week 1 (0.91%) week 2 (1.04%), Expiratory Reserve Volume (ERV) resulting in week 1 (1.14%) week 2 (1.24%), Inspiratory Reserve Volume (IRV) resulting in week 1 (0.66%) week 2 (1.04%) and Inspiratory Capacity (IC) resulting in week 1 (0.69%) week 2 (0.71%), together with decreasing respiratory times; inspiratory time (Ti) resulting in week 1 (-0.31%) week 2 (-0.38%), expiratory time (Te) and total inspiratory and expiratory time (Tt) resulting in week 1 (-0.24%) week 2 (-0.31%). Conclusions: A home pulmonary treatment plan with OPEP and POWERbreathe Plus® shows a clear improvement in lung function in subjects with ABPA, bronchiectasis, and asthma, thus improving quality of life.